1984 After February 24th: A Philosophical Rereading of Orwell’s Novel - Zlatyslav Dubniak (Kyiv-Mohyla Humanities Journal)
The article offers a philosophical rereading of George Orwell’s novel 1984 in the context of the Russian-Ukrainian war, in particular after the full-scale invasion of Ukraine on February 24th, 2022. In recent decades, the dystopia of the English writer has become not only a model of literary criticism of totalitarianism but also the subject of constant falsifications and censorship for Russian propagandists. This study aims to clarify the primary philosophical content of Orwell’s novel and its heuristic potency to expose the sociopolitical situation in contemporary Russia. The author of the article turns to biographical descriptions and philosophical interpretations of the novel in the works of leading Western scholars to finally draw reasonable analogies between the dystopian world of 1984 and the contemporary Russian Federation.